PENGGUNAAN METODE ALGORITMA WAGNER WITHIN DALAM UPAYA PENGENDALIAN PERSEDIAAN SCRAP BESI DI PT. XYZ - Somadi, Somadi; Septa, Syah Rajendra Hari; Juita, Nila Dahlia (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2020)
The research objective is to determine the total size of the lot of iron scrap orders, and the total cost of the company's inventory before and after carrying out the method of controlling iron scrap inventory using the Wagner Within Algorithm method. Demand forecasting uses the Single Moving Averge, Weight Moving Average, and Exponential Smoothing methods. Based on the results of the study, the total lot size of iron scrap material orders is smaller than the size of previous lot orders without using the inventory control method, which is 15,362 tons per year. Total inventory of Rp. 105,076,125,840 and the total cost is more optimal when compared with the total cost of inventory with the company system that is Rp. 109,734,165,840 so that the company can save costs by Rp. 4,658,040,000.